The Reverse Matthew Effect: Consequences of Retraction in Scientific Teams - Jin, Ginger Zhe; Jones, Benjamin; Lu, Susan Feng; Uzzi, Brian (The Review of Economics and Statistics, 2019)
Teamwork pervades modern production, yet teamwork can make individual roles difficult to ascertain. The Matthew effect suggests that communities reward eminent team members for great outcomes at the expense of less eminent team members. We study this phenomenon in reverse, investigating credit sharing after damaging events. Our context is article retractions in the sciences. We find that retractions impose little citation penalty on the prior work of eminent coauthors, but less eminent coauthors experience substantial citation declines, especially when teamed with eminent authors. These findings suggest a reverse Matthew effect for team-produced negative events. A Bayesian model provides a candidate interpretation.